Visible‐Light‐Mediated Oxygenation Reactions using Molecular Oxygen. Issue 4 (27th February 2017) - Bian, Changliang; Singh, Atul K.; Niu, Linbin; Yi, Hong; Lei, Aiwen
Abstract: As a clean, inexpensive and widely available energy source, visible light has received increased attention and research interest from all around the world. In the field of synthetic organic chemistry, more and more groups are pursuing visible‐light‐mediated chemical transformations. Various types of reactions using visible light as an initiator have been described in the past several decades (mainly in the past ten years). It has become a powerful tool for constructing new chemical bonds and has shown wide application prospects in organic synthesis. In addition, there have been several reviews summarizing the progress of visible‐light‐mediated syntheses from different points of view. This review provides a summary on the development of visible‐light‐mediated oxygenation reactions using molecular oxygen, and can be used as a reference guide to direct the design of new reactions. Abstract : Oxygenation reactions promoted by visible light : The development of visible‐light‐mediated oxygenation reactions utilizing molecular oxygen has been briefly summarized based on the type of newly formed chemical bond. Synthetic organic methodologies and mechanistic studies have been discussed.